Net Production and Consumption of Fluorescent Colored Dissolved Organic Matter by Natural Bacterial Assemblages Growing on Marine Phytoplankton Exudates - Romera-Castillo, Cristina (American Society for Microbiology, 2011)
An understanding of the distribution of colored dissolved organic matter (CDOM) in the oceans and its role in the global carbon cycle requires a better knowledge of the colored materials produced and consumed by marine phytoplankton and bacteria. In this work, we examined the net uptake and release of CDOM by a natural bacterial community growing on DOM derived from four phytoplankton species cultured under axenic conditions. Fluorescent humic-like substances exuded by phytoplankton (excitation/emission [Ex/Em] wavelength, 310 nm/392 nm; Coble's peak M) were utilized by bacteria in different proportions depending on the phytoplankton species of origin. Furthermore, bacteria produced humic-like substances that fluoresce at an Ex/Em wavelength of 340 nm/440 nm (Coble's peak C). Differences were also observed in the Ex/Em wavelengths of the protein-like materials (Coble's peak T) produced by phytoplankton and bacteria. The induced fluorescent emission of CDOM produced by prokaryotes was an order of magnitude higher than that of CDOM produced by eukaryotes. We have also examined the final compositions of the bacterial communities growing on the exudates, which differed markedly depending on the phytoplankton species of origin. Alteromonas and Roseobacter were dominant during all the incubations on Chaetoceros sp. and Prorocentrum minimum exudates, respectively. Alteromonas was the dominant group growing on Skeletonema costatum exudates during the exponential growth phase, but it was replaced by Roseobacter afterwards. On Micromonas pusilla exudates, Roseobacter was replaced by Bacteroidetes after the exponential growth phase. Our work shows that fluorescence excitation-emission matrices of CDOM can be a helpful tool for the identification of microbial sources of DOM in the marine environment, but further studies are necessary to explore the association of particular bacterial groups with specific fluorophores.